Formulation of Tinidazole as an Oral Suspension Dosage Form - Lubna A. Sabri; Halah T. Sulayman; Dina W. Ameen (Al-Mustansiriyah Journal of Pharmaceutical Sciences, 2013)
Tinidazole is an effective drug for the treatment of amoebiasis, giardiasis and anaerobic bacterial infections, it has a long half-life and it is practically insoluble in water thus it is suitable for suspension dosage form. This study was carried out to prepare an acceptable suspension through studying the effect of different types and concentrations of suspending agent such as sodium carboxyethyl cellulose, xanthan gum, sodium alginate and avecil (RC 591). The effect of these suspending agents was studied in 0.1N HCL and at 37°C. The obtained results were utilized to formulate different suspensions. The release rate, sedmintation volume and resuspendability were evaluated for these formulas. The formula which gave best release and optimum sedimentation volume was chosen as the best formula. The result showed that the release rate of the drug was dependent on the type and concentration of suspending agent. The best one was that containing 0.5%, xanthan gum as a suspending agent. The rheology and expiration date were evaluated for this formula. The expiration date of the prepared suspension was about 2.2 years. The suspension of tinidazole was also extemporaneously prepared from Fasigyn® tablets. The prepared extemporaneous suspension should be used within 7 days after preparation.